Umbilical Cord Blood Gas Analysis, Obstetric Performance and Perinatal Outcome - Ferreira, Cátia Sofia; Melo, Ângela; Fachada, Ana Helena; Solheiro, Helena; Nogueira Martins, Nuno (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Objective To analyze if umbilical artery pH (pHua) ≤7.00 and umbilical artery blood deficit (BDua) ≥12.00 mmol/L are good predictors of adverse neonatal outcomes.Methods This was an observational, longitudinal and retrospective cohort study, conducted at the department of obstetrics and gynecology of Centro Hospitalar Tondela Viseu between September 2013 and September 2015. Total cohort and subgroup analysis were performed: group A—women with umbilical cord blood gas analysis (UCBGA) performed for non-reassuring fetal cardiotocographic patterns, placental abruption, or shoulder dystocia; and group B—all the others. Assays were made with the software SPSS for Windows, Versions 20.0 and 21.0 (IBM Corp., Armonk, NY, USA).Results A total of 428 UCBGAs met the inclusion criteria. The group analysis revealed an association between group A and pHua ≤7.00, as well as between BDua ≥12.00 mmol/L and 1st minute Apgar score ≤4 (p = 0.011). After the application of the logistic regression models in the total cohort analysis, pHua ≤7.00 had an impact in the occurrence of acute neonatal hypoxia (odds ratio [OR]: 6.71; 95% confidence interval [CI]: 1.21–37.06; p = 0.029); multiparous women had a higher risk of delivering a newborn with first minute Apgar score ≤4 and acute neonatal hypoxia (OR: 5.38; 95% CI: 1.35–21.43; p = 0.017; and OR: 2.66; 95% CI: 1.03–6.89, p = 0.043, respectively); women who had urologic problems during pregnancy had a higher risk of delivering a newborn with 5th minute Apgar score ≤7 (OR: 15.17; 95% CI: 1.29–177.99; p = 0.030); and shoulder dystocia represented a 15 times higher risk of acute neonatal hypoxia (OR: 14.82; 95% CI: 2.20–99.60; p = 0.006).Conclusion The pHua and the BDua are predictors of adverse neonatal outcome, and UCBGA is a useful tool for screening newborns at risk. Universal UCBGA should be considered for all deliveries, as it is an accurate screening test for neonatal hypoxia.
Keywords: Umbilical Cord Blood Gas Analysis; delivery; morbidity; neonatology